Analisis Kohesi dan Koherensi Pada Antologi Cerpen Hari-Hari Hello Sebagai Alternatif Bahan Pembelajaran Dalam Menulis Karangan Narasi Bagi Siswa Sekolah Dasar - Damayanti, Irma; Widjojoko, Widjojoko; Wardana, Deni (Didaktika, 2021)
This research is needed because in learning to write narrative essays, students are expected to be able to make a compelling and interesting narrative essay so that the contents of the message in the essay can be conveyed well to the reader and do not get bored when reading it. From these difficulties, this research will discuss the cohesion and coherence contained in the anthology of Hari-Hari Hello short story. After that this research discusses the use of cohesion and coherence in short stories which can be used as learning materials to write narrative essays made by the teacher and as a reference for students in writing narrative essays so that they can write essays coherently and interestingly. This research was conducted using a qualitative approach. The existing data were analyzed using content analysis. Researchers limit the research subjects to only the Rumus Keriting short stories and Hello Potter short stories. The results of the research obtained from the results of the analysis are the cohesion and coherence of the Rumus Keriting short stories and the Hello Potter short stories. Thus, it can be concluded that the short story Rumus Keriting and the short story Hello Potter are a solid short story because there is cohesion and coherence used in the story and it is possible to make these short stories as learning materials to write narrative essays.